Role of the Bed Nucleus of the Stria Terminalis in PTSD: Insights From Preclinical Models - Miles, Olivia W.; Maren, Stephen (Frontiers in Behavioral Neuroscience, 2019)
Post-traumatic stress disorder (PTSD) afflicts approximately 8% of the United States population and represents a significant public health burden, but the underlying neural mechanisms of this and other anxiety- and stressor-related disorders are largely unknown. Within the last few decades, several preclinical models of PSTD have been developed to help elucidate the mechanisms underlying dysregulated fear states. One brain area that has emerged as a critical mediator of stress-related behavioral processing in both clinical and laboratory settings is the bed nucleus of the stria terminalis (BNST). The BNST is interconnected with essential emotional processing regions, including prefrontal cortex, hippocampus and amygdala. It is activated by stressor exposure and undergoes neurochemical and morphological alterations as a result of stressor exposure. Stress-related neuro-peptides including corticotropin releasing factor (CRF) and pituitary adenylate cyclase activating peptide (PACAP) are also abundant in the BNST, further implicating an involvement of BNST in stress responses. Behaviorally, the BNST is critical for acquisition and expression of fear and is well positioned to regulate fear relapse after periods of extinction. Here, we consider the role of the BNST in stress and memory processes in the context of preclinical models of PTSD.